Trust, Citizenship, and Civil Society (Sapta Darma and His Struggle to get State Recognition) - Ngatipan; Abid Nurhuda (MultiTech Publisher, 2023)
This research attempts to explore the dynamics of the struggle of adherents of the belief in God in Indonesia, especially adherents of Sapto Darmo to obtain their civil rights (Civil Society). The fulfillment of civil rights from the Dutch colonial era until the New Order era still seems selective, there are even indications of systematic efforts to hinder the emergence of this Civil Society. The debate over the issue of eliminating the 'religion column' on KTPs for adherents of beliefs ended with the issuance of a Constitutional Court Decision as an amendment to Law Number 23 of 2006 concerning Population Administration is a bright spot for its implementation Civil Society in Indonesia. Even though at the idealistic level this is over, at the practical level there are still many obstacles. In fulfilling this Civil Society, the state as the sole authority holder does not only put forward the purely juridical legal aspects but also the aspects of the state political contract that must be considered.